2022
DOI: 10.1111/ejh.13745
|View full text |Cite
|
Sign up to set email alerts
|

Pixantrone in patients with relapsed/refractory diffuse large B‐cell lymphoma: A real‐life, retrospective, multicenter trial on behalf of the “RTL” (Regional Tuscan Lymphoma network)

Abstract: Introduction Pixantrone is a novel aza‐anthracenedione with antineoplastic activity, currently approved for multiply relapsed/refractory diffuse large B‐cell lymphoma (DLBCL), even if real‐life data are limited. Methods We investigated pixantrone efficacy and safety in clinical practice, as 3rd or 4th line therapy. We retrospectively analyzed a cohort of 37 R/R DLBCL patients managed in 8 Tuscan onco‐hematological centers. Pixantrone, 50 mg/m2, was administered on days 1, 8, 15 of a 28 days cycle for up to 6 c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(11 citation statements)
references
References 34 publications
0
11
0
Order By: Relevance
“…A total of 300 publications were identified using the described search strategies. After removing all duplicates and excluding studies that did not meet the inclusion criteria, a total of 25 journal articles -18 original articles, [8][9][10][11]14,[21][22][23][24][25][26][27][28][29][30][31][32][33] 3 letters to the editor, [34][35][36] 3 short reports, 13,37,38 and 1 case report 39 and 5 conference publications [40][41][42][43][44] were included in the systematic review. All the 30 studies allowed the data collection of 37 treatment regimens for R/R MCL patients.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…A total of 300 publications were identified using the described search strategies. After removing all duplicates and excluding studies that did not meet the inclusion criteria, a total of 25 journal articles -18 original articles, [8][9][10][11]14,[21][22][23][24][25][26][27][28][29][30][31][32][33] 3 letters to the editor, [34][35][36] 3 short reports, 13,37,38 and 1 case report 39 and 5 conference publications [40][41][42][43][44] were included in the systematic review. All the 30 studies allowed the data collection of 37 treatment regimens for R/R MCL patients.…”
Section: Resultsmentioning
confidence: 99%
“…1 Nevertheless, it is considered useful to validate the efficacy and safety of treatments in real-world studies to adopt them in routine clinical practice. In this regard, the real-world evidence currently available on R/R MCL treatments is scarce and scattered, [8][9][10][11][12][13][14] and it is often difficult to compare due to the diversity of the approaches and the patients' characteristics. Therefore, this systematic review aimed to collect, synthesize, and describe the characteristics and treatment outcomes of patients with R/R MCL after receiving a second or subsequent line of therapy in the real-world setting.…”
Section: Introductionmentioning
confidence: 99%
“…20 In our initial report, we retrospectively analyzed data regarding pixantrone efficacy and toxicity in daily clinical practice, according to the approved indications by the Italian medicines agency. 21,22 In this post-hoc analysis, we selectively investigated clinical characteristics and long-term survival of DLBCL patients who achieved a CR with pixantrone. According to this amendment of the study, we included patients with available clinical follow-up, who achieved a CR with pixantrone, administered as third or fourth line therapy.…”
Section: Introductionmentioning
confidence: 99%
“…In our initial report, we retrospectively analyzed data regarding pixantrone efficacy and toxicity in daily clinical practice, according to the approved indications by the Italian medicines agency 21,22 . In this post‐hoc analysis, we selectively investigated clinical characteristics and long‐term survival of DLBCL patients who achieved a CR with pixantrone.…”
Section: Introductionmentioning
confidence: 99%
“…In our study, pixantrone demonstrated a rapid-onset efficacy with mild toxicity but a limited PFS. 10 The strength as BT would be its safety, with the possibility of being used both before and after apheresis. Moreover, it was successfully used in a heavily pretreated case of our cohort as a bridge to allogeneic transplantation.…”
mentioning
confidence: 99%